Choose hope : your role in waging peace in the nuclear age - Krieger, David, c1942.; Gage, Richard L.; Ikeda, Daisaku (Santa Monica, CA : Middleway Press, 2002)
Shares Eastern and Western perspectives on nuclear weapons and the threat of nuclear war in the twenty-first century, featuring a dialogue between American David Krieger and Japanese Daisaku Ikeda on what can be done to encourage a peaceful future.
Translation of: Kibo no sentaku.
Includes bibliographical references (p. 181-186) and index.
Adult.
Adult
Keywords: Peace; Peace